DIFFICULTIES MET BY SECONDARY SCHOOLS’ PUPILS AT UNIVERSITY: CASE OF ADVENTIST UNIVERSITY OF LUKANGA (DRC) - Edeline BAYIKERTA Kasay, (IJRDO- Journal of Educational Research, 2021)
When making this article, our objective consists to show secondary degrees the diversity of issues to be oriented. May these matters be treated differently and in another hand, it meant to know these diversities in orders to adapt the action or orientation.The orientation or the guidance is the help brought to individuals in their effort to make the intelligent choice and judicious as well as to adapt adequately to diverse situations of life.The orientation helps the youth to make an individual life fully satisfied and socially efficient. Note that society is made of great responsibility to lead children and youth as well those who have the congenital deficiency (low mental from birth) due to illness that hinder to realize the activities able to respond to their own needs and the society’s as well.After our studies about the school orientation our results show us that the bad orientation of the low cycle commonly called nowadays seventh and eighth forms should be the cause of most of failures in G1 at the high level.We think that with the new reform, we shall be witness of improvement in school orientation with a test that will determine intellectual Quotient (IQ) of each leaner in order to undertake the section of their level that will lead to good choice of the faculty to be followed after the secondary studies.